Determinants of import of tobacco in Malaysia / Natasha Badaruddin - Badaruddin, Natasha (Faculty of Business and Management, 2007)
Over the past 30 years, 1970 - 2000 world tobacco consumption, production and trade have increased steadily. Malaysia basically imported the unmanufactured tobacco from a country such as Brazil, China, Indonesia, Thailand, USA and others. As a general the annual tobacco demand is met by local production and the balance is imported. However, this paper attempts to explain and prove the determinants of import of tobacco in Malaysia. Besides that, the main purpose of this project paper is to analyze the trend of import of tobacco. This project paper will identify the determinants that can lead to import of tobacco in Malaysia since it is one of the international trade being done for Malaysian economy. In this study, an attempt is made to assess the certain variable that assume can be the determinants import of tobacco such as production of tobacco, the consumption of tobacco, population in Malaysia, the tobacco planted area and also the exchange rate. The study will take in consideration all the variables and prove the significant at the end of the paper.